First case report of pulmonary and cutaneous nocardiosis caused by Nocardia mexicana in Iran. Issue 4 (23rd April 2019) - Shokri, Darioush; Motalebirad, Tahereh; Jafarinia, Morteza; Azadi, Davood; Ghaffari, Kazem
Abstract : Background . Nocardia are aerobic partially acid-fast bacteria that are environmentally ubiquitous. This group of bacteria causes a rare bacterial infection of either the lungs (pulmonary) or body (systemic) that usually affects immunocompromised individuals. Nocardia mexicana was first isolated in 2004 from a patient with chronic bronchitis. However, there have been few reports on the clinical significance of this organism up to now. We herein report the first cases of N. mexicana in patients with pulmonary and cutaneous infection from Iran. Case presentation. A 57-year-old man was admitted to hospital due to a cutaneous wound on his left foot, fever, weakness, persistent cough and chest pain. At first, due to clinical examination and laboratory test, the patient was diagnosed as having tuberculosis. However, PCR of Mycobacterium tuberculosis was negative from broncho-alveolar lavage (BAL) samples. Direct PCR of BAL was performed for this patient and according to the clinical examinations and microbiological evaluations; the micro-organism was identified as N. mexicana and was isolated from both BAL and the wound. Finally, the patient was treated with linezolid and amikacin. Conclusions. The infections, with actinomycetes such as Nocardia, are easily neglected or misdiagnosed due to the fastidious nature of the organism and the inadequate microbiological experience of laboratories in the hospitals of developing countries. This case shows that hospitals should consider a better laboratory protocol to deal with the clinical cases in which fastidious organisms, and in particular Nocardia, are involved.